Identifikasi Faktor Ibu Dengan Perdarahan Post Partum - Frisca Dewi Yunadi; Rully Andhika; Rochany Septiyaningsing (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2019)
Postpartum hemorrhage is bleeding that occurs immediately after labor exceeds 500 cc which is divided into primary bleeding and secondary bleeding. Untreated postpartum bleeding can lead to shock and can cause death. Cases of post partum hemorrhage in Cilacap Hospital are very high. In 2017 there were 73 cases of post partum hemorrhage and in 2018 there were 72 cases. The purpose of this study was to identify maternal factors with the incidence of post partum hemorrhage in the Cilacap Hospital in the period 2017-2018. The design of this study was to use a descriptive survey research design with a cross sectional time approach with quantitative methods. The sample in this study used a total sampling of 143 samples. Data analysis using univariate analysis. The results of the study showed that the majority of mothers who experienced post partum hemorrhage at the age of not at risk (77.6%), riskless parity (61.5%), distance at risk of birth (69.9%), no history of SC (96, 5%), anemia (72.2%), and no history of previous postpartum hemorrhage (95.1%). Suggestions for health workers more often provide education to Fertile Age Couples related to the assessment program so that the pregnancy is planned and there are no bleeding problems. Keywords: post partum hemorrhage, age, parity, distance of labor, anemia. ABSTRAK Perdarahan postpartum adalah kehilangan darah melebihi 500cc yang terjadi segera setelah persalinan yang dibagi menjadi perdarahan primer dan perdarahan sekunder. Akibat dari perdarahan post partum salah satunya adalah syok dan dapat menyebabkan kematian. Angka kejadian perdarahan postpartum di RSUD Cilacap sangat tinggi. Pada tahun 2017 ada sebanyak 73 kasus perdarahan post partum dan tahun 2018 ada 72 kasus. Tujuan dari penelitian ini adalah untuk mengidentifikasi faktor ibu yang mengalami perdarahan post partum di RSUD Cilacap periode 2017-2018. Desain penelitian ini adalah menggunakan rancangan penelitian survey deskriptif dengan pendekatan waktu cross sectional dengan metode kuantitatif. Sampel dalam penelitian ini sebanyak 143 sampel. Analisa data menggunakan Analisa univariat. Hasil penelitan memperlihatkan paling banyak ibu yang mengalami perdarahan post partum pada usia tidak beresiko (77,6%), paritas tidak beresiko (61,5%), jarak persalinan beresiko (69,9%), tidak ada riwayat SC (96,5%), anemia (72,2%), dan tidak ada riwayat perdarahan postpartum sebelumnya (95,1%). Saran untuk tenaga kesehatan adalah lebih sering meberikan edukasi pada Pasangan Usia Subur berkaitan dengan program kehamilan agar kehamilan terencana dan tidak ada resiko perdarahan. Kata Kunci : Perdarahan Post Partum, Umur, Paritas, Jarak Persalinan, Anemia